Impaired processing speed in categorical perception: Speech perception of children who stutter - Bakhtiar, Mehdi (PLoS One, 2019)
There have been controversial debates across multiple disciplines regarding the underlying mechanism of developmental stuttering. Stuttering is often related to issues in the speech production system; however, the presence and extent of a speech perception deficit is less clear. This study aimed to investigate the speech perception of children who stutter (CWS) using the categorical perception paradigm to examine their ability to categorize different acoustic variations of speech sounds into the same or different phonemic categories. In this study, 15 CWS and 16 children who do not stutter (CWNS) completed identification and discrimination tasks involving acoustic variations of Cantonese speech sounds in three stimulus contexts: consonants (voice onset times, VOTs), lexical tones, and vowels. The results showed similar categorical perception performance in boundary position and width in the identification task and similar d' scores in the discrimination task between the CWS and CWNS groups. However, the reaction times (RTs) were slower in the CWS group compared with the CWNS group in both tasks. Moreover, the CWS group had slower RTs in identifying stimuli located across categorical boundaries compared with stimuli located away from categorical boundaries. Overall, the data implied that the phoneme representation evaluated in speech perception might be intact in CWS as revealed by similar patterns in categorical perception as those in CWNS. However, the CWS group had slower processing speeds during categorical perception, which may indicate an insufficiency in accessing the phonemic representations in a timely manner, especially when the acoustic stimuli were ambiguous.